1997
DOI: 10.1111/j.1558-5646.1997.tb03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Phylogeography of North American Highland Fishes: A Test of the Pleistocene Vicariance Hypothesis

Abstract: The highland fish fauna of eastern North America consists of Appalachian and Ozark centers of endemism separated by the intervening Glacial Till Plains. Clades within these areas are more closely related phylogenetically to each other than to clades occurring in the intervening formerly glaciated region, suggesting that the Pleistocene glaciations fragmented a widespread highland region and its associated fauna. Alternatively, it is possible that these faunal assemblages predate the glaciations or that recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A higher compatibility with sympatric host populations compared with allopatric host populations may be expected where different species or genetically distinct populations of fish are available to mussel populations, so that local adaptations might evolve (Eckert, 2003;Riusech & Barnhart, 2000;St. John White et al, 2017;Strange & Burr, 1997). Compatibility has been shown to decrease as isolation between the mussel source and fish source increased (St. John White et al, 2017) and host suitability was found to be higher on host fish within the natural distribution range of the mussel (Taeubert et al, 2010), but this tendency towards higher success on sympatric host fish is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…A higher compatibility with sympatric host populations compared with allopatric host populations may be expected where different species or genetically distinct populations of fish are available to mussel populations, so that local adaptations might evolve (Eckert, 2003;Riusech & Barnhart, 2000;St. John White et al, 2017;Strange & Burr, 1997). Compatibility has been shown to decrease as isolation between the mussel source and fish source increased (St. John White et al, 2017) and host suitability was found to be higher on host fish within the natural distribution range of the mussel (Taeubert et al, 2010), but this tendency towards higher success on sympatric host fish is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…Episodic flooding, on the other hand, allowed antecedent streams to down-cut, with headwaters subsequently being eroded and basins concomitantly expanding, with large-scale dispersals being promoted [29]. These alterations (i.e., captures, diversions, beheadings; [30]) not only extended the distribution of fishes into adjacent basins [31], but also facilitated hybridization [32,33,34], a process that has confound both taxonomists and managers (and continues to do so).…”
Section: The Synergy Between Tectonism and Climatementioning
confidence: 99%
“…Similar patterns were observed at smaller scales among drainages within the study region, as reported for White River crayfish (Fetzner & DiStefano, 2008). While the Lower White and Black rivers are certainly contemporary large-river habitats, both would have been much larger pre-Pleistocene when together they represented the main channel of the Old Mississippi River (Mayden, 1988;Strange & Burr, 1997). This large-river habitat would have separated the eastern and western highland tributaries, with inhospitable habitat for upland species.…”
Section: Paleohydrology In the White River Systemmentioning
confidence: 99%
“…Organisms within such dendritic networks are demonstrably impacted by the physical structure of the habitat (Peterson et al, 2013;White et al, 2020), with genetic relatedness as a surrogate for the underlying structural hierarchy (Hughes et al, 2009). While this is most apparent within the contemporary structure of river networks, their historic structure, i.e., paleohydrology, also serves to bookmark genetic diversity (Mayden, 1988;Strange & Burr, 1997). Moreover, the hierarchical complexity of these networks will likewise dictate population processes, as reflected within genetic diversities and divergences (Chiu et al, 2020;Hopken et al, 2013;Thomaz et al, 2016).…”
mentioning
confidence: 99%